The Effects of Chia Defatted Flour as a Nutritional Supplement in C57BL/6 Mice Fed a Low-Quality Diet - Lucini Mas, Agustín (2024)
Today, consumption of diets rich in saturated fat and fructose, associated with a variety of metabolic deregulations, has increased. The aim of this study was to evaluate the effect of dietary supplementation with a residue of defatted chia seed on a diet with low nutritional quality. To do this, C57BL/6 male mice were fed with the Control (C), Low-Nutritional-Quality (LNQ), or supplemented-with-chia-defatted-flour (LNQ+C) diets. After 12 weeks, the glucose and lactate levels were determined in the serum, liver, and kidney, along with reactive oxygen species (ROS) levels, antioxidant enzyme activity, reduced glutathione (GSH), and protein oxidation (AOPP). The LNQ diet increased the glucose and lactate levels (+25% and +50% approx. in the liver, with respect to the control group) and generated oxidative stress by modifying the levels of ROS and the activity of antioxidant enzymes, causing oxidative damage to proteins (+12% in the liver, with respect to the control). Chia supplementation helped to restore the glucose to control levels and modulate the endogenous antioxidant system, resulting in a decrease in protein oxidation products with no differences compared to the control group. In conclusion, supplementation with chia showed beneficial effects on the general health of mice, even when fed a low-nutritional-quality diet.